1989
DOI: 10.2118/15515-pa
|View full text |Cite
|
Sign up to set email alerts
|

New Findings on Leak Resistance of API 8-Round Connectors

Abstract: This paper covers research funded by the API Production Research Advisory Committee (PRAC) on leak resistance of ~PI 8-~ou~d connectors. It details the sensitivity of leak resistance to variations in makeup turns, pipe diameter, grade, and applied tep-Slon. FIndIngs show that the leak resistance of the connector relative to pipe-body ratings increases with the number of makeup turns ~nd decreases as diameter and yield strength increase. Finally, tension is found to lower leak resistance in a manner that render… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Several studies have proposed different criteria based on SFCP to define leakage resistance. Figure 4 illustrates two proposed criteria to determine if fluid penetration occurs: 1) fluid penetration occurs if fluid pressure exceeds SFCP; 2) fluid penetration occurs if SFCP is zero [13]. Schwind et al [14,15] suggested two parameters to quantify sealability: 1) average pressure on the stab flank and 2) average pressure on stab flank normalized by the internal pressure.…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have proposed different criteria based on SFCP to define leakage resistance. Figure 4 illustrates two proposed criteria to determine if fluid penetration occurs: 1) fluid penetration occurs if fluid pressure exceeds SFCP; 2) fluid penetration occurs if SFCP is zero [13]. Schwind et al [14,15] suggested two parameters to quantify sealability: 1) average pressure on the stab flank and 2) average pressure on stab flank normalized by the internal pressure.…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
“…API recommendations only consider effects of make-up torque, neglecting effects of axial loading and material plasticity, known to be relevant for leakage resistance [15]. Loading sequence also influences sealability [13,15]. Studies recommend the following load sequence: make-up, followed by axial load, and finally internal pressure.…”
Section: Review Of Fe Modelling Of Leakage In Casing Connectionsmentioning
confidence: 99%
“…Pesquisas recomendam avaliar a estanqueidade com a seguinte sequência de cargas: torque de aperto, seguido de carga axial e finalmente pressão interna. Esta ordem de cargas replica as condições de serviço de conexões, pois a coluna de revestimento é constantemente solicitada pela carga axial na pressurização (SCHWIND et al, 1995;WOOLEY, 1989). Os citados autores comentam que aplicar pressão interna antes da tração, ou aplicação simultânea de pressão interna e tração, como em testes de tampa fechada, levam à superestimação da estanqueidade.…”
Section: Avaliação Da Estanqueidadeunclassified
“…Como discutido anteriormente, novos trabalhos apontam ao aporte da pressão hidrostática no selo (GOODMAN; MITCHELL; KALIL, 2019). Porém, trabalhos apontam que ensaios com tampa fechada e testes nos quais pressões internas são aplicadas previamente a cargas axiais conduzem à superestimação do selo (SCHWIND et al, 1995;WOOLEY, 1989). Autores apontam também que a avaliação da estanqueidade é crítica após aplicação da tração, o que corrobora os resultados obtidos na avaliação das pressões nos flancos opostos da conexão API 8 Round 9 5/8" L80 47lb/ft.…”
Section: Pressões Nos Flancos Opostosunclassified